Language Contact Studies in Nepal: Trends and Prospects - Gautam, Bhoj Raj (Gipan, 2025)
This paper is a review of major language contact studies in Nepal especially focusing on Noonan (2003) and Gautam (2021) based on different aspects. Furthermore, the paper aims to summarize language contact studies in Nepal and discusses its trends and suggests possible areas of language contact studies, which is based on various secondary sources published in this area of study. However, language contact studies can be carried out either focusing on various socio-cultural processes, conversational constraints and role of different pragmatic elements in languages that shape different language ideologies, which motivate contacts or outcomes of language contact based on lexical and grammatical levels of language. Furthermore, it visualize the future trends and prospects to shape Nepal’s language policy in different diversified contexts.